Ask Question
5 August, 17:18

Describe the transformation from the graph of f (x) = x+8 to the graph of g (x) = x-3

A.) the graph g (x) = x-3 is the result of translating the graph of f (x) = x+8 down 11units.

B.) the graph g (x = x-3 is the result of translating the graph of f (x) = x+8 up 11units.

C.) the graph g (x) = x-3 is the result of translating the graph of f (x) = x+8 down 5 units

D.) The graph g (x) = x-3 is the result of translating the graph of f (x) = x+8 up 5 units.

+3
Answers (1)
  1. 5 August, 17:26
    0
    A.)

    Step-by-step explanation:

    Translations are as follows: Up is + on Y axis, down is - on Y axis. Right is + on X axis and left is - on X axis.

    The function f (x) = x+8 is translated to (0,8) since their is no number in a bracket with x (example: f (x) = (x-2) + 5 would be (2,5) since the X axis is taken as the opposite sign).

    g (x) = x-3 translates to (0,-3) which is 11 units down from f (x)
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Describe the transformation from the graph of f (x) = x+8 to the graph of g (x) = x-3 A.) the graph g (x) = x-3 is the result of ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers